2017
DOI: 10.1177/0040517517700197
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between washing parameters, fabric movement, and wrinkling in a top-loading washer

Abstract: Abstract:Easy care for clothing is increasingly important, but the major problem is still the severe wrinkles formed on garments after machine washing. In this research, orthogonal tests and the analysis of variance (ANOVA) at a 95% confidence level were used to determine the critical parameters that affect fabric smoothness. We developed a video capturing and processing system for dynamic measurements of fabric in a top-loading washer to find the relationship between fabric movement and wrinkling performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Experimental studies of fabric movement in a rotating drum are reported in some cases of washing machine research [23][24][25][26][27], but rarely in case of tumble dryer research. Recently Wei et al [28] conducted measurements with different fabric types and sizes, drying loads and drum speeds to determine fabric movement patterns and their effect on the performance of a vented tumble dryer.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies of fabric movement in a rotating drum are reported in some cases of washing machine research [23][24][25][26][27], but rarely in case of tumble dryer research. Recently Wei et al [28] conducted measurements with different fabric types and sizes, drying loads and drum speeds to determine fabric movement patterns and their effect on the performance of a vented tumble dryer.…”
Section: Introductionmentioning
confidence: 99%
“…An important factor in the loss of repellency of the protective materials against pesticides is the water temperature and the movements during washing used in garments. These facts affect the efficiency of cleaning agents and affect the protection of cotton fabrics as well [51].…”
Section: Washing and Permeation Processesmentioning
confidence: 99%
“…[38][39][40] A lumped transient model with a semi-empirical character is generated to study the mechanism of detergent transportation between the inner drum and through the textiles in a top-loading washer 28 .Only Liu studied how fabric movement influences fabric wrinkle during top-loading washing. 41 Little work has been carried out on how mechanical action influence fabric wrinkling during front loading washing.…”
Section: Introductionmentioning
confidence: 99%